2005
DOI: 10.1111/j.1526-4610.2005.05025.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Patterns of Medication Use of Migraneurs in Latin America From 12 Cities in 6 Countries

Abstract: Migraine is a common disorder in Latin American urban communities imposing significant burden on individuals, families, and communities. The magnitude of the impact and the range of activities affected by migraine are similar to those of previous reports in other regions. The preponderance of nonprescription medications and the scarcity of migraine-specific triptans from the study findings are especially striking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
37
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 22 publications
14
37
1
1
Order By: Relevance
“…For this study we only used the migraine section. It has been previously tested in a healthy Mexican population [11][12][13]. This questionnaire measures some sociodemographic data and disability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study we only used the migraine section. It has been previously tested in a healthy Mexican population [11][12][13]. This questionnaire measures some sociodemographic data and disability.…”
Section: Methodsmentioning
confidence: 99%
“…We used the MIDAS questionnaire to evaluate headache-related disability [14]. The presence of migraine in the last year was ascertained according to the validated questionnaire [11]. The percentage of patients who refused to participate was 5%.…”
Section: Methodsmentioning
confidence: 99%
“…The first, prior to the formulation of the IHS criteria [4], demonstrated it in 40% of 50 migraineurs studied [5]; the second, in a more recent study in a larger patient population, revealed the presence of osmophobia in 25% of migraineurs [6]. In a recent epidemiologic study of a Latin American patient population, osmophobia in migraineurs was said to be "almost always" present in 47.7% of subjects [7]. No study has ever been conducted that considered this phenomenon in relation to the different forms of primary headache.…”
Section: Giorgio Zanchin Filippo Dainese Federico Mainardi Edoardo Mamentioning
confidence: 99%
“…Although the disability of migraine in the United States, France, and Latin America is similar, just 6% of the migraineurs in France and 2% in Latin America were current preventive users. 23,24 Our study has limitations. First, we used a validated questionnaire to diagnose migraine just in those with self-defined severe headaches.…”
mentioning
confidence: 99%